Radar systems and radio aids to navigation - Sen, A. K. (Mercury Learning & Information, 2019)
This comprehensive reference explains the many processes needed for creating radar systems and navigation aids. Selected topics include antennas, radar targets, Doppler radar, atmospheric probing, mathematical preliminaries, hyperbolic navigation, aircraft homing systems, and more.
Keywords: Aids to navigation.; Radar in navigation.; Radio in navigation.; elektronické knihy; electronic books